Construction and Study of Amine Electrodes Based on Membranes Containing Sulfonic Compounds as Active Materials with Different Plasticizers in PVC Matrix Membranes - Na.ssory, N.S.; Musleh, R.M.; Abbas, A.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Several amine liquid selective electrodes were prepared based on two active materials, phenol sulfonic acid and l ,2-dihydroxy-3,5- disulfonic acid disodium salt with several plasticizers, di-n-butyl phthalate(ORPH), tri-n-butyl phosphate (TBP) and a-nitro phenyl octyl ether (NPOE). Electrode parameters were studied including, concentration range, detection limit, slope, life time, response time and pH effect. Excellent results were obtained based on n-hyptyl methyl amine with DBPH and phenol sulfonic acid as an active material. The slope was 56.g mY/decade, concentration range was ranged from 1oÂ·’ M to 1o-4 M with correlation coefficient of 0.9999, detection limit of 6 x l o-) M and pH ranged from 5.6 to less than one. Electrode based on tri-hutyl amine as a secondary amine gives a slope 48.4 mV/decade with good results for the other parameters, but for dccyl amine as a primary runine give very poor response. Electrodes based on secondary and tertiat)’ amines gives very poor response because incompatibility of NOPE with active material and pvc. Also the study was carried out for a second active material 1,2-dihydroxy- 3,5-disulfonic acid disodium salt and also a good results were obtained.